The role of KCl in the high temperature corrosion of alloy Sanicro 28 - Pettersson, Carolina (My University, 2003)
The high temperature corrosion behaviour of the austenitic alloy Sanicro 28 treated with small amounts of KCl was investigated at 600°C in 5% O2 and 5% O2 + 40% H2O using furnace experiments. The exposure time was 1 to 168 hours. The corrosion products were qualitatively analyzed using X-ray diffraction, Environmental scanning electron microscopy with EDX analysis and Auger electron spectroscopy. Quantitative analysis was performed by gravimetry. The corrosion rate of Sanicro 28 is strongly accelerated by KCl in both environments studied. The results show degradation of the protective, chromium rich oxide by KCl forming K2CrO4, leading to breakaway corrosion. (The highest corrosion rate was observed in 5% O2). Sanicro 28 show better resistance to KCl induced corrosion than 304L. The dominating corrosion product on Sanicro 28 exposed in the presence of KCl was corundum type oxides, e.g. (Cr,Fe)2O3. In addition spinel type oxides, e.g. Ni(Cr,Fe)2O4 was identified. K2CrO4 formed in both atmospheres.
Keywords: Kemi; Materialteknik; Miljöteknik; Chemical Sciences; Materials Engineering; Environmental engineering